Benefit of first‐pass complete reperfusion in thrombectomy is mediated by limited infarct growth. (12th October 2020) - Ben Hassen, W.; Tordjman, M.; Boulouis, G.; Bretzner, M.; Bricout, N.; Legrand, L.; Benzakoun, J.; Edjlali, M.; Seners, P.; Cordonnier, C.; Oppenheim, C.; Turc, G.; et al.
Abstract: Background and Purpose: The number of clot retrieval attempts required to achieve complete reperfusion by mechanical thrombectomy impacts functional outcome in acute ischaemic stroke (AIS). Complete reperfusion [expanded Treatment In Cerebral Infarction (eTICI) score = 3] at first pass (FP), is associated with the highest rates of favorable outcome compared to complete reperfusion by multiple passes. The aim of the present study was to investigate the relationship between FP complete reperfusion and infarct growth (IG). Methods: Anterior AIS patients with baseline and 24‐h diffusion‐weighted magnetic resonance imaging were included from two prospective registries. IG was measured by voxel‐based segmentation of initial and 24‐h diffusion‐weighted imaging lesions. IG and favorable 3‐month modified Rankin Scale (mRS) score (≤ 2) were compared between patients in whom complete reperfusion (eTICI 3) was achieved with a single pass (FP group) and those for whom multiple passes were required (MP group), after matching for confounding factors. Mediation analysis was performed to examine the association between FP and 3‐month mRS score, with IG as mediating variable. Results: A total of 200 patients were included, of whom 118 (28.9%) had FP complete reperfusion. In case–control analysis, the FP group had lower IG than the MP group [8.7 (5.4–12.9) ml vs. 15.2 (11–22.6) ml, respectively; P = 0.03). Favorable outcome was higher in the FP population compared to a matched MP population (70.9% vs. 53.2%, respectively; P = 0.04). FP compete reperfusion (eTICI 3) was independently associated with favorable outcome in multivariable regression analysis [odds ratio 1.86, 95% confidence interval (CI) 1.01–4.39; P = 0.04]. The effect of complete reperfusion at FP on functional outcome was explained by limited IG in mediation analysis [indirect effect: −0.32 (95% CI −0.47 to −0.09)]. Conclusion: Complete reperfusion at FP is independently associated with significant decrease in IG compared to complete reperfusion by multiple attempts, explaining better functional outcomes.